Fort Bema (P-Parysów) in Warsaw – adaptation to the city recreation function - Gleń, Piotr; Głuszek, Cezary (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
This article deals with the idea of ​​synergistic integration of architectural and natural heritage – on the example of a former fortress building. Transformations of monuments located in close urban development become necessary – due to their tourist, cognitive and historical attractiveness. Architecture militaris objects cannot currently continue their original purpose. In order for an object to function in contemporary realities, it is necessary to give it contemporary functions – which becomes a sine qua non condition for their preservation and protection. Doing so is the introduction of contemporary additions to historical structures. The problem arises in the agreement between the interests of the user, the investor and the requirements that the designer must meet. An additional component of the entire process of adaptation/revalorization are also aspects related to the discussion on the possibility of permissible changes, transformations in line with the evolution of conservation thought. The research was focused on the archival query of the previous conservation studies and the local inspection of the area in order to verify the condition of the object and the degree/scope of adaptation works carried out. On the example of Fort Bema, where a functional program was implemented, concerning the adaptation of the fort to the space of urban leisure and recreation, the authors of the text presented effective design and conservation activities. In conclusion, it was hypothesized that such a course of action could also be used in post-fortress complexes located in less urbanized areas, e.g. in the Dęblin Fortress.